Implementasi teknologi digital untuk meningkatkan kualitas sepatu pada Industri Kecil dan Menengah - Caecilia Sri Wahyuning (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2019)
One important aspect in shoe design is a matter of comfort, which is determined by dimensions and the shape of shoe last which is influenced by the design of the master shoe last. The use of 3D scanners, 3D printers, and CAD / CAM systems in the process of master shoe last design and production of shoe last can improve the quality of shoe products. However, the application of technology to the IKM implies the need to increase HR capabilities and substantial investment. This indicates the need for involvement of government and institutions / R & D institutions or universities. Therefore, to improve the design of university competencies in mastering technology, curriculum needs to be designed that refers to the competence of designer work in accordance with the progress / development of digital technology in the process of design and production. Key words: industry 4.0, Small and Medium Industries, master shoe last, quality